Securing well-being with the advent of climate hazards: Case of forest-dependent communities in a landscape in the Congo Basin - Chia, E.L.; Tiani, A.M.; Sonwa, D.J.; Pérez Terán, A.S. (Emerald Publishing Limited, 2016)
– This paper aims to examine the contribution of forests resource systems to the different aspects of community well-being, the implications of climate variability on the different sources of well-being and further identifies direct and indirect social and policy opportunities relevant for communities to enhance their capabilities in the face of climate variability and change in the Tri-National de la Sangha landscape of Cameroon.– It illustrates on data collected from focus group discussions and from 151 households randomly selected in three villages to operationalize the conceptual links between community well-being and vulnerability.– The study shows that vulnerability to climate change interferes with community strategies to achieve well-being, in addition to non-climatic processes which are both internal and external to communities. The study further indicates that healthy forest ecosystems provide opportunities for the local folks to build assets, improve food security, improve health and reduce risks. However, this requires capacity building and the channeling of resources to the local level, in addition to win–win sectoral policy amendments.– Biophysical methods required to complement community perceptions on the suitability of forest resource systems to climate variability.– This paper argues that appropriate strategies which aim at improving well-being needs to capture the role of forest ecosystems, climate change risks and uncertainty and macroeconomic and social processes.– This study contributes to the literature on the relationship between climate risk and the well-being of forest communities. This is relevant for practitioners and policy makers to reflect on the risk of climate change and the rationale for conserving forest resources for community well-being in the post-2015 Millennium Development Goals conclusions.